Self-Regulation as A Mediator Between the Effect of Mental Accounting on Decision Satisfaction of Car Purchases - Asri Rejeki; Tatik Suryani; Siti Sulasmi (Universitas Ahmad Dahlan, 2019)
This study aims to determine the effect of mental accounting on satisfaction with purchase decision, using self-regulation as a mediator. Previous studies about post-purchase have focused on decision satisfaction - despite the latter being an antecedent of satisfaction. This study attempts to view decision satisfaction through the lense of mental accounting, namely how consumers code and categorize income as well as evaluate spendings. This is a quantitative research that studies consumers who bought cars in Jakarta and Surabaya. The sample consist of 316 participants, recruited through convenient sampling technique. The measuring instrument used is a modified Decision Satisfaction Questionnaire (SWD) by Holmes-Roy, 3-item Self-Regulation Questionaire to measure Self-Regulation to buy, and 2-item Mental Budgeting Questionnaire to measure mental accounting. These are all in the form of a 5-item Likert scale. The validity of the item is done using the Rasch model. Data analysis was performed using partial least squares PLS-SEM with the use of Software SmartPLS 3. The findings indicate that self-regulation acts as a mediator between mental accounting and decision satisfaction. Decision Satisfaction as First order is affected directly by the second order, which is â€œGood Enoughâ€, â€œNot Availableâ€, â€œMove Onâ€ and â€œHappy with the decisionâ€. Self-Regulation as a mediator variable positioned as First order is influenced directly by the Second order, namely â€œStrategyâ€, â€œControlâ€, â€œObjectiveâ€, â€œEvaluationâ€, â€œProgressâ€, and â€œFirmnessâ€. Mental Accounting as First order is influenced directly by Second order, namely â€œFrameâ€, â€œCategoryâ€, and â€œEvaluationâ€.Â Keyword: decision satisfaction, mental accounting, self-regulation